2022
DOI: 10.1002/ctm2.658
|View full text |Cite
|
Sign up to set email alerts
|

Interventional‐ and amputation‐stage muscle proteomes in the chronically threatened ischemic limb

Abstract: Background Despite improved surgical approaches for chronic limb‐threatening ischemia (CLTI), amputation rates remain high and contributing tissue‐level factors remain unknown. The purpose of this study was twofold: (1) to identify differences between the healthy adult and CLTI limb muscle proteome, and (2) to identify differences in the limb muscle proteome of CLTI patients prior to surgical intervention or at the time of amputation. Methods and results Gastrocnemius muscle was collected from non‐ischemic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 59 publications
4
18
0
Order By: Relevance
“…Consistent with our previous reports, 24 , 25 we found that CLTI patients displayed significant impairment in mitochondrial oxidative phosphorylation. In the present study, we used a novel CK clamp system to test the mitochondrial oxidative phosphorylation function across a range of physiologic relevant energy demands to mimic a stress test that ranges from rest to exercise.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with our previous reports, 24 , 25 we found that CLTI patients displayed significant impairment in mitochondrial oxidative phosphorylation. In the present study, we used a novel CK clamp system to test the mitochondrial oxidative phosphorylation function across a range of physiologic relevant energy demands to mimic a stress test that ranges from rest to exercise.…”
Section: Resultssupporting
confidence: 93%
“…Careful examination of a recently curated proteomics dataset from CLTI limb muscle indicated that S100A8/A9 proteins were significantly elevated in CLTI muscle compared with non-PAD control participants ( Fig 1 , A ). 25 This finding was confirmed using mRNA analysis ( Fig 1 , B ). S100A8/A9 are calcium binding proteins that belong to the S100 family.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…A component of walking performance is related to muscular strength, power, and endurance. Various groups have documented pathological abnormalities within the skeletal muscle of PAD patients (66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80). Few clinical studies have employed objective measures of muscle strength or power in PAD patients, particularly in the context of randomized clinical trials.…”
Section: Discussionmentioning
confidence: 99%